Pengaruh Evaluasi Pembelajaran Aktif Terhadap Motivasi Belajar Siswa - Laura Andarini Pasaribu; Nurlaili Afsari Tanjung; Putri Irmayani; Syahrial Syahrial (Lembaga Pengembangan Kinerja Dosen, 2024)
Learning is a complex and diverse process that involves interactions between students, teachers, and the learning environment. The main goal of learning is to improve students' understanding and skills, and motivate them to learn. One learning approach that is emerging and increasingly popular is active learning. In this article, the effect of active learning on student learning motivation will be evaluated. Learning is an important process in the development of education in Indonesia. The main goal of learning is to increase students' learning motivation, which can influence their ability to achieve optimal results. One learning method that has been proven effective in increasing students' learning motivation is active learning. In this article, we will evaluate the effect of active learning on students' learning motivation. Learning is an important aspect of the educational process which has a direct influence on students' learning motivation. In recent years, active learning approaches have become popular among educators as an effective method for increasing students' learning motivation. Evaluation of the influence of active learning on student learning motivation is important to understand the successes and shortcomings of this method. This article will evaluate the effect of active learning on student learning motivation using a professional approach. This research method uses the Systematic Literature Review (SLR) technique. The Systematic Literature Review technique is carried out in five stages, namely: 1. formulating research questions, 2. mapping and searching for articles that are in accordance with the research questions asked, 3. classifying and evaluating the articles that have been collected, 4. summarizing article, 5. interpret the findings in the article. The search for articles carried out by researchers was regarding the Effect of Active Learning Evaluation on Student Learning Motivation. The database used is based on the database contained in Google Scholar, Garuda, Open Journal System (OJS). The literature used in the research, namely publications within the last 510 years, is not optimal so it needs to continue to be the focus of this research. The articles collected were then reviewed and analyzed so that they could provide an overview of the research questions discussed in this study.